Дипломати в античних державах Північного Причорномор’я - Скржинська, М.В. (Український історичний журнал, 2017)
Уперше зібрано епіграфічні й літературні джерела зі згадками про дипломатичну діяльність еллінів в Ольвії, Херсонесі, Боспорі. Автор показує, як високо
цінували заслуги громадян, котрі успішно виконували дипломатичні доручення,
а також характеризує завдання, що їх вирішували місцеві й іноземні посли. This is the first complete compilation of Olbian, Chersonesеan and Bosporean
ambassadors
in lapidary inscriptions and works of ancient writers. The position of
ambassador was at the same range as other high level magistracies. The Greeks elected
ambassadors out of educated and wealthy citizens, sometimes out of influential
foreigners. The ambassadors added their own money to the monetary funds issued by
the state, and sometimes themselves fully covered their trip and accommodation expenses
in other cities. In the ancient States of the Northern the Black Sea Coast the
highest state authorities took the ambassadors of Greek city-states, Pontus, Egypt
and Rome. Foreign ambassadors received for the success of their activity the honorary
decrees and various benefits. Ambassador‘s function were considered as an important
mission, for the successful implementation of which ambassadors received
several awards.